Pull Out Resistance of Glued in Rod Parallel to Grain in Laminated Bamboo - Karyadi Karyadi; Wahyu Risky Nurpitasari; Nindyawati Nindyawati (Program Studi Teknik Sipil Fakultas Teknik Universitas Lancang Kuning, 2022)
Research on hollow cross section beams and columns made of laminated bamboo has been carried out. So that the two elements can be assembled into a building structure, it is necessary to do connection. Glued in rod is a new connecting tool whose mechanical properties still need to be studied. For this reasons this research was conducted. To achieve this objective, an experiment was conducted with the independent variables (1) the distance between the two edges, (2) the diameter of the threaded rod, and (3) the embedded length. The results showed that (1) the greater the distance between the two edges, the greater the pull out strength of the glued in rod, (2) the larger the diameter of the threaded rod, the greater the pull out of the glued in rod, (3) the greater the embedded length of the threaded rod, the stronger the pull out of glued in rod, (4) the value of the slip modulus is affected by variations in diameter and embedded length but is not affected by the distance between the two edges. The greatest pull out strength, which is 34.85kN, is achieved at a glued in rod diameter of 12mm with an edge distance of 4.5d and a embedded length of 6d, while the lowest value is 14.38kN lies in steel rods with a diameter of 8mm with a embedded length of 5d and a distance of two edges is 2.5d. The highest slip modulus or the highest stiffness value of 9.75kN/mm is achieved at a diameter of 12 mm with an embedded length of 6d and a distance of two edges of 3.50d. The smallest slip modulus value of 3.75kN/mm was achieved at a diameter variation of 8 mm with an embedded length of 5d and a distance of two edges 2.5d